RESEARCH OF THE MARKET OF SCIENTIFIC PRODUCTION OF THE PRICARPATE DHSGDS (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. In today's market conditions for the vast majority of scientists and institutions with state ownership, it is quite difficult, but an important step is to transform their worldview, motivations and strategy of action in innovative market-oriented directions. Effective and inefficient sellers (including IPOs), products and services compete in the market without any weakening. Encourage and motivate the consumer to choose your product - a challenge that requires careful attention and a systematic approach. The presence of seeds on the domestic market of rapeseed in the context of the number and range of varieties and hybrids of winter and spring rape is characterized by the expansion of market capacity, the dominance of foreign breeding innovations over domestic developments, sharp competition in the winter rape segment and low competition in the rape segment.  In general, the ratio of old and new varieties to the culture is 0.6: 1.0. The purpose of the article Marketing analysis of the conjuncture of the plant varieties market as a model object of science-intensive production of a scientific institution. Results. Due to the fact that the main high-tech products of the Carpathian SSGDS are plant varieties, namely cruciferous crops, we have focused our efforts on research of the rapeseed market as a model object. The marketing analysis of market conditions (conjuncture analysis) of science-intensive products of the Precarpathian SSGDS on the example of rape as a model object was conducted.  Allocated segments of the plant varieties market in Ukraine.  The offer of varieties of rape plants is formed mainly by commercial companies, organizations, firms, that is, predominantly private breeding. Conclusions. The offer on the market of seed of plant varieties, as well as other offers of goods in a market economy, depends on its own market price, the cost price of the produced seed of a variety, the price of seeds of varietal substitutes, the number of sellers on the market and the state measures on market regulation.
Keywords: innovation, market research, market research, market of plant varieties